Accurate protein-ligand binding free energy estimation using QM/MM on multi-conformers predicted from classical mining minima - Farzad Molani; Art E. Cho (Communications Chemistry)
Abstract Accurate prediction of binding free energy is crucial for the rational design of drug candidates and understanding protein-ligand interactions. To address this, we have developed four protocols that combine QM/MM calculations and the mining minima (M2) method, tested on 9 targets and 203 ligands. Our protocols carry out free energy processing with or without conformational search on the selected conformers obtained from M2 calculations, where their force field atomic charge parameters are substituted with those obtained from a QM/MM calculation. The method achieved a high Pearson’s correlation coefficient (0.81) with experimental binding free energies across diverse targets, demonstrating its generality. Using a differential evolution algorithm with a universal scaling factor of 0.2, we achieved a low mean absolute error of 0.60 kcal mol- 1. This performance surpasses many existing methods and is comparable to popular relative binding free energy techniques but at significantly lower computational cost.